ANNETTE SPIRO, DAVID GANZONI (eds.) - The Working Drawing: The Architect’s Tool - Fernández Morales, Angélica (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
ANNETTE SPIRO Y DAVID GANZONI (eds.) Zúrich: Park Books, 2013, 328 págs. Idioma: inglés